Advancing human and social dimensions in balanced scorecards for GCC corporations: a nuanced approach - Emad Awadallah (Cogent Economics & Finance, 2024)
In today's corporate world, where accountability extends beyond mere economic output to embrace social, environmental, and cultural contributions, it is imperative to reevaluate traditional performance measurement systems. This research emphasizes the critical need to embed human and social metrics into these systems. This need is particularly pronounced in the dynamic corporate world, where Environmental, Social, and Governance (ESG), Diversity, Equity, and Inclusion (DEI) criteria and sustainability imperatives are increasingly at the forefront. Rooted in Stakeholder Theory, this study contends that corporations must broaden their performance metrics. Such integration is essential to maintaining competitiveness, responsibility, and relevance in a culturally diverse and rapidly changing environment. Our empirical investigation involved 89 GCC firms and 201 senior executives, alongside 21 semi-structured interviews from the same pool of senior executives who had completed the survey. The findings highlight a significant gap between existing performance measurement frameworks and the demands of the contemporary business ethos, marked by the sociocultural nuances of the GCC. A notable trend among participants was the desire for more comprehensive metrics within the BSC that genuinely reflect a firm's societal impact. However, this ambition faces significant barriers, including resistance to change, training and development needs, data availability and quality, and the alignment of these metrics with overarching organizational strategy. These findings emphasize the complex yet crucial task of advancing the human and social dimensions in BSCs, presenting both opportunities and challenges for GCC corporations in their journey toward more inclusive and comprehensive performance measurement. This research provides significant insights into the evolving nature of performance measurement systems by integrating human and social dimensions within the Balanced Scorecard (BSC) framework for corporations in the Gulf Cooperation Council (GCC) region. The study's findings highlight a critical gap in current performance metrics, which often overlook the importance of Environmental, Social, and Governance (ESG) and Diversity, Equity, and Inclusion (DEI) considerations. By employing both quantitative and qualitative methods, this research underscores the necessity for GCC firms to broaden their performance evaluation criteria to remain competitive and socially responsible in a rapidly changing business landscape. The implications of this study are profound, offering actionable recommendations for organizations to enhance their strategic alignment and operational efficiency by incorporating broader, more inclusive metrics. This work contributes to the global discourse on sustainable business practices and provides a model for other regions aiming to integrate comprehensive performance measures into their strategic frameworks.
Keywords: 330; Balanced Scorecard (BSC); Diversity; Equity; and Inclusion (DEI); Environmental; Social; and Governance (ESG); GCC firms; performance metrics